2011
DOI: 10.1007/s11240-011-0046-0
|View full text |Cite
|
Sign up to set email alerts
|

Production of monoterpenoids and aroma compounds from cell suspension cultures of Camellia sinensis

Abstract: Cell suspension cultures of Camellia sinensis were established in 250 ml shake flasks. Flasks contained 50 ml liquid medium of either Murashige and Skoog (MS), N/5 MS or Heller medium containing different levels of 6-benzyladenine (BA) (0.05-2 mg l -1 ), 2,4-dichlorophenoxyacetic acid (2,4-D) (1-10 mg l -1 ), and sucrose (10-50 g l -1 ). Moreover, the pH of the medium was varied from 5.2-6.2. In addition, cultures were subjected to light irradiation as well as to complete darkness. Following optimization of ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…Generally, for a certain plant, the optimal solid medium for callus growth is also suitable for its cell suspension in liquid culture without agar . However, tea produces large quantities of polyphenols in response to the high concentration of inorganic salts in MS basal medium, leading to browning of the callus. , Therefore, in this study, two kinds of media were tested to compare the growth status of callus and the color of the cell suspension. The average growth rate of cells was 16.66% in B5 basal media and 15.77% in MS basal media (Figure S2); however, the cell suspension culture liquid and part of the callus were brown in MS basal media.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, for a certain plant, the optimal solid medium for callus growth is also suitable for its cell suspension in liquid culture without agar . However, tea produces large quantities of polyphenols in response to the high concentration of inorganic salts in MS basal medium, leading to browning of the callus. , Therefore, in this study, two kinds of media were tested to compare the growth status of callus and the color of the cell suspension. The average growth rate of cells was 16.66% in B5 basal media and 15.77% in MS basal media (Figure S2); however, the cell suspension culture liquid and part of the callus were brown in MS basal media.…”
Section: Resultsmentioning
confidence: 99%
“…anthraquinones (hypericin, pseudohypericin), phloroglucine derivate (hyperforin) in Hypericum sp. shoot cultures (Coste et al, 2011), flavonoid (rutin) in Morus alba in vitro cultures (Lee et al, 2011), terpenoids in Camellia sinensis suspension cultures (Grover et al, 2012), and alkaloid (galanthamine) production in in vitro cultures of three Amaryllidaceae species (El Tahchy et al, 2011). We had documented this relationship in our earlier studies on the accumulation of linear furanocoumarins in A. majus (Ekiert, 1993; and P. sativa cultures (Ekiert and Gomółka, 2000 b), and on the accumulation of lignans in S. chinensis cultures (Szopa and Ekiert, 2011;2015).…”
Section: Discussionmentioning
confidence: 99%
“…anthraquinones (hypericin, pseudohypericin), phloroglucine derivate (hyperforin) in Hypericum sp. shoot cultures (Coste et al 2011), flavonoid (rutin) in Morus alba in vitro cultures (Lee et al 2011), terpenoids in Camellia sinensis suspension cultures (Grover et al 2012), and alkaloid (galanthamine) production in in vitro cultures of three Amaryllidaceae species (El Tahchy et al 2011). Studies performed in our laboratory have confirmed the effects of NAA and BA concentrations in L-S medium on free phenolic acids accumulation in in vitro cultures of R. graveolens (Ekiert et al 2009) and its subspecies R. graveolens ssp.…”
Section: Discussionmentioning
confidence: 99%